{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

# 16a - Lecture 16 1 Legendre Polynomials First we note that...

This preview shows pages 1–3. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Lecture 16 1 Legendre Polynomials First, we note that n ! ( n- 2 j )! j ! j ! = ( n 2 j )( 2 j j ) , and so P n ( t ) = b n/ 2 c X j =0- 1 4 j n j 2 j j (1- t 2 ) j t n- 2 j . h Interlude: Recall that f n ( x,y,z ) = b n/ 2 c X j =0- 1 4 j n j 2 j j ( x 2 + y 2 ) j z n- 2 j . We can determine homogenous degree n polynomials that are invariant under rotation about any axis: say the axis determined by the unit vector u . Then, using the geometric properties of the cross product and the dot product, we find that these polynomials are all scalar multiples of f n ( r ) = b n/ 2 c X j =0- 1 4 j n j 2 j j || u × r || j ( u · r ) n- 2 j . i Recall that ∂ z f n = nf n and (2 n + 1) zf n ( x,y,z )- n ( x 2 + y 2 + z 2 ) f n- 1 ( x,y,z ) = ( n + 1) f n +1 ( x,y,z ) . From these properties of f n come the following properties of P n : nt n P n ( t ) + (1- t 2 ) P n ( t ) = nP n- 1 ( t ) (1) and ( n + 1) P n +1 ( t )- (2 n + 1) tP n ( t ) + nP n- 1 ( t ) = 0 . (2) Next, we show that P n satisfies the Legendre equation d dt [(1- t 2 ) dT dt ] + n ( n + 1) T = 0 . 1 From (1) it follows that (1- t 2 ) dP n dt = n [ P- n- 1( t )- tP n ( t )], and so d dt [(1- t 2 ) dP n dt ] = n [ P n- 1 ( t )- tP n ( t )]- nP n ( t ) . Now all that remains is to show that tP n ( t )- P n- 1 ( t ) = nP n ( t ). Multiply the LHS of this equation by (1- t 2 ), giving (1- t 2 )[ tP n ( t...
View Full Document

{[ snackBarMessage ]}

### Page1 / 6

16a - Lecture 16 1 Legendre Polynomials First we note that...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online